Impact of the COVID-19 pandemic on vaccination coverage in children in Brazil: A literature review - Abreu, Igor Rafael (2022)
Immunization is one of the most successful and cost-effective public health interventions for children that has helped to reduce child mortality worldwide. In view of the above, the present study aimed to review the impact of the COVID-19 pandemic on vaccination coverage in children in the literature. This is a literature review, carried out between October 2021 and May 2022. The electronic search was performed in the PubMed and Lilacs databases. In addition, the CAPES journal portal was accessed in order to search for dissertations and theses that complemented the work. The search was performed using a combination of the search terms “vaccination”, “children”, “impact”, “COVID-19” and the Boolean operator “AND”. The COVID-19 pandemic has imposed a reality of confinement around the world, impacting all sectors, especially health, including vaccination coverage of children. The pandemic has shown negative effects on vaccination efforts and programs, where studies report that millions of babies received delayed vaccines. This situation has brought challenges to the application of the National Vaccination Calendar, especially for children up to 12 months of age who have had their vaccines delayed, showing that in emergency situations additional strategies are needed, such as greater public awareness and vaccination booster campaigns.